2010
DOI: 10.1016/j.ymgme.2010.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 comparison of a novel ammonia scavenging agent with sodium phenylbutyrate in patients with urea cycle disorders: Safety, pharmacokinetics and ammonia control

Abstract: Glycerol phenylbutyrate (glyceryl tri (4-phenylbutyrate)) (GPB) is being studied as an alternative to sodium phenylbutyrate (NaPBA) for the treatment of urea cycle disorders (UCDs). This phase 2 study explored the hypothesis that GPB offers similar safety and ammonia control as NaPBA, which is currently approved as adjunctive therapy in the chronic management of UCDs, and examined correlates of 24-hour blood ammonia.Methods-An open-label, fixed sequence switch-over study was conducted in adult UCD patients tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 9 publications
7
80
0
Order By: Relevance
“…This compound has been shown to reduce protein mislocalization in diseases such as cystic fibrosis, cerebral ischemic injury, diabetes, Alzheimer's disease, and familial Parkinson's disease (28)(29)(30)(31)(32), and it has been approved for clinical use in patients with cystic fibrosis and to treat urea cycle disorders (28,33). Our results have potential clinical relevance, as they point out a pathological mechanism of desmin protein aggregation effected by plectin deficiency.…”
Section: Figure 10mentioning
confidence: 51%
“…This compound has been shown to reduce protein mislocalization in diseases such as cystic fibrosis, cerebral ischemic injury, diabetes, Alzheimer's disease, and familial Parkinson's disease (28)(29)(30)(31)(32), and it has been approved for clinical use in patients with cystic fibrosis and to treat urea cycle disorders (28,33). Our results have potential clinical relevance, as they point out a pathological mechanism of desmin protein aggregation effected by plectin deficiency.…”
Section: Figure 10mentioning
confidence: 51%
“…113 It also functions as a chemical chaperone because of the preferential hydration of the exposed polypeptide backbones and side chains of partially unfolded structures. 114,115 PBA is now used in the clinical setting for the treatment of diseases associated with protein misfolding, such as ␣1-antitrypsin deficiency and cystic fibrosis. 114,115 Ozcan et al have shown that chemical chaperones reduce ER stress and restore glucose homeostasis in a mouse model of type 2 diabetes.…”
Section: Chemical Er Chaperonesmentioning
confidence: 99%
“…114,115 PBA is now used in the clinical setting for the treatment of diseases associated with protein misfolding, such as ␣1-antitrypsin deficiency and cystic fibrosis. 114,115 Ozcan et al have shown that chemical chaperones reduce ER stress and restore glucose homeostasis in a mouse model of type 2 diabetes. 116 Erbay et al have shown that ER modification by chemical chaperones in macrophages and adipocytes has therapeutic efficacy against atherosclerosis in mouse models.…”
Section: Chemical Er Chaperonesmentioning
confidence: 99%
“…GPB has the same mechanism of action as sodium PB, but is a pre-pro drug consisting of phenylbutyric acid (PBA) linked to glycerol. Following hydrolysis by pancreatic lipases, PBA is released and converted to the active moiety, phenylacetic acid (Lee et al 2010;McGuire et al 2010;Monteleone et al 2013). In clinical trials, GPB has been shown to provide effective ammonia control in adult and pediatric UCD patients (Lichter-Konecki et al 2011;Smith et al 2013;Diaz et al 2013;Berry et al 2014).…”
Section: Introductionmentioning
confidence: 99%